Pengembangan Usaha Desain Mandiri Berbasis Teknologi Di Dusun Durensari, Desa Kembangkuning, Kecamatan Cepogo Kabupaten Boyolali - Aulia, Meilita; Hanafi, Muhammad; Prastiwi, Mentari Dwi; Ghofardhan, Muhammad; Sulistiyowati, Arrin (Universitas Pahlawan Tuanku Tambusai, 2025)
The technology-based graphic design training on the Canva application carried out in Durensari Hamlet aims to improve the skills of the community, especially youth and MSME players, in utilising design technology to support the promotion of local products. This activity includes socialisation, discussion, questions and answers and training that can provide a basic understanding of entrepreneurship and the practical use of graphic design applications. Participants were taught to create works such as posters, business logos, brochures, and pricelists to strengthen their marketing strategies. The results of the training showed an increase in participants' skills in using the Canva application as an effective simple design tool. This training also opened up new opportunities for participants to develop a graphic design service business, thus supporting the development of local MSMEs. In addition, this activity succeeded in introducing graphic design-based technology to people who were previously unfamiliar, thus reducing the technology gap. With the enthusiasm of the participants, this training is expected to be the first step in increasing community independence through digital-based entrepreneurship. For maximum results, further assistance is needed so that participants can continue to develop their skills.